Assessing attention towards plants: Development and first steps to the validation of the Hidden Object Picture Instrument (HOPI) - Peter Pany; Benno Dünser; Dawn Lorraine Sanders; Lisa Anna Pernausl; Kerstin Kranner; Manuel Wenzlik; Dagmar Fister; Andrea Möller; Peter Lampert (PLoS ONE, 2026)
Public awareness of plants remains limited despite their essential ecological and societal roles. A major challenge in addressing this issue is the absence of validated instruments that measure attentional-memory processes regarding plants. This study introduces the Hidden Object Picture Instrument (HOPI), a novel visual tool designed to assess plant-directed attention in complex natural scenes. The development involved three sub-studies: (1) designing and validating a landscape image based on biodiversity data, (2) examining attentional mechanisms using eye-tracking, recall, and species identification, and (3) testing known-groups validity among students and botanical experts. Free listing combined with salience analysis revealed cognitive prominence and recall patterns for different object types. Eye-tracking showed no correlations between object size, time to first fixation, total fixation duration, average fixation time, and number of fixations and recall salience for plants and animals. Experts exhibited higher plant salience and more specific naming, while students mainly used general terms (e.g., “tree,” “field”). These findings indicate that plants are often perceived as background elements rather than distinct entities. The HOPI provides a transparent, replicable method for assessing visual attention to plants and offers valuable applications for research and education. It represents a first step towards understanding and fostering plant awareness as part of environmental education and biodiversity conservation.